2003
DOI: 10.2166/wst.2003.0200
|View full text |Cite
|
Sign up to set email alerts
|

Water quality problems associated with intermittent water supply

Abstract: A controlled study was conducted in Lebanon over a period of 12 months to determine bacterial regrowth in a small network supplying the Beirut suburb of Naccache that had a population of about 3,000. The residential area, which is fed by gravity, is supplied twice a week with chlorinated water from two artesian wells of a confined aquifer. A significant correlation was detected between the turbidity and the levels of heterotrophic plate count bacteria (HPC) in the samples from the distribution network as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 10 publications
2
36
0
Order By: Relevance
“…Private storage is a consequences of residents' private investment in infrastructure [6,33]. Nevertheless, private storage causes poor water quality [46,55,110], pressure surges in the system [13,48], and consumer overdraw [2,23,35,50,76,114]. Additionally, some authors found that private storage wastes water [23,35,70,81,128], while others found that in systems with more reliable supply, water storage did not result in more water use [18,47].…”
Section: Discussionmentioning
confidence: 99%
“…Private storage is a consequences of residents' private investment in infrastructure [6,33]. Nevertheless, private storage causes poor water quality [46,55,110], pressure surges in the system [13,48], and consumer overdraw [2,23,35,50,76,114]. Additionally, some authors found that private storage wastes water [23,35,70,81,128], while others found that in systems with more reliable supply, water storage did not result in more water use [18,47].…”
Section: Discussionmentioning
confidence: 99%
“…degradation of the EPDM, itself, and reaction of carbon black. The degradation of the EPDM may be associated with oxidation, chlorination, crosslinking and so forth, since the city water contains air, and it is mixed with chlorine dioxide, sodium hypochlorite and calcium hypochlorite as a disinfectant to prevent proliferations of bacteria and virus [6,7]. Furthermore, the city water is frequently heated with a boiler to keep warm, so that the degradation of the EPDM seal may be accelerated at the elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have established that unsafe water is directly associated with pollution sources, inadequate or lack of treatment, poor water distribution systems, and illegal and nonengineered water connections (Mintz et al 1995;Ahmed et al 1998;Semenza et al 1998;Sobsey 2002;Clasen and Bastable 2003;Sobsey et al 2003;Tokajian and Hashwa 2003). Further, water at the household level may be exposed to sources of contamination due to unsanitary practices in relation to its collection, storage, and handling (Han et al 1989;Jensen et al 2002;Clasen and Bastable 2003;Clasen and Mintz 2004;Wright et al 2004).…”
Section: Introductionmentioning
confidence: 99%